2010
DOI: 10.1007/s11738-010-0532-8
|View full text |Cite
|
Sign up to set email alerts
|

Physiological changes and essential oil composition of clary sage (Salvia sclarea L.) rosette leaves as affected by salinity

Abstract: Since soil salinity is a widespread problem, we proposed to focus on its effect on seedling growth, mineral composition and particularly on essential oil composition known to be reliable to abiotic conditions. Clary sage seedlings were hydroponically cultivated under different salt concentrations (0, 25, 50, and 75 mM NaCl). The dry biomass and the mineral element contents were determined. The essential oils were extracted and analyzed by GC and GC-MS. Results showed that growth was reduced by 42% at 75 mM. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 31 publications
5
27
0
3
Order By: Relevance
“…In addition to alterations in the percentage of major compounds, the different NaCl concentrations induced an increased number of compounds as identified in the EO of all the NaCl treatments ( Table 2). The same was observed by Taarit et al (2011), who reported an increased amount of compounds in Salvia esclarea L. Some compounds such as cis-verbenol (1.18%), estragole (0.62%) and p-cymene (0.19%) were exclusively found at 200 mM NaCl, the highest salt concentration. High production of compounds at high salinity concentrations probably occurred due to the increased enzymatic activity for the EO biosynthesis (Taarit et al, 2010;Khalid and Cail, 2011).…”
Section: Effects Of Salt Stress On Yield and Chemical Composition Of supporting
confidence: 81%
“…In addition to alterations in the percentage of major compounds, the different NaCl concentrations induced an increased number of compounds as identified in the EO of all the NaCl treatments ( Table 2). The same was observed by Taarit et al (2011), who reported an increased amount of compounds in Salvia esclarea L. Some compounds such as cis-verbenol (1.18%), estragole (0.62%) and p-cymene (0.19%) were exclusively found at 200 mM NaCl, the highest salt concentration. High production of compounds at high salinity concentrations probably occurred due to the increased enzymatic activity for the EO biosynthesis (Taarit et al, 2010;Khalid and Cail, 2011).…”
Section: Effects Of Salt Stress On Yield and Chemical Composition Of supporting
confidence: 81%
“…The decline of diterpenes content in response to salinity has been previously reported in clary sage (Salvia scalrea), where a significant decrease of manoyl oxide and phytol was observed in hydroponic culture containing 25, 50, and 75 mM NaCl [41]. In our case, it seems that the reduction in marrubiin content is likely due to the inhibition of its correspondent biosynthesis enzymes, namely diterpenes synthases [41] in response to salinity.…”
Section: Marrubiin Contentsupporting
confidence: 84%
“…In our case, it seems that the reduction in marrubiin content is likely due to the inhibition of its correspondent biosynthesis enzymes, namely diterpenes synthases [41] in response to salinity. Another possible explanation is that the decline of marrubiin could be linked with the accelerated senescence induced by salt stress as reported in Cistus creticus [43].…”
Section: Marrubiin Contentmentioning
confidence: 57%
“…By contrast, K ? content was decreased in both plant parts as was found in Carthamus tinctorius (Gadallah 1996), Glycine max (Ç içek and Ç akirlar 2008), Origanum majorana (Baatour et al 2010), Solanum (Daneshmand et al 2010) and Salvia sclarea (Ben Taârit et al 2011). The decrease in K ?…”
Section: Discussionmentioning
confidence: 63%
“…Alternatively, this phenomenon could be associated with to both a faster osmotic adjustment and a slower turgor loss in the roots (da Silva et al 2008). Support to this assumption has been recently given by Ben Taârit et al (2011) who studied the effect of salt stress on some physiological and biochemical parameters of Salvia sclarea and found that salt treatment (25 and 50 mM) did not affect the water content in the roots suggesting therefore, that plants subjected to salt stress are able to undergo osmotic adjustment. This physiological response is crucial for salt-stressed plants and evolved two main processes: accumulation of ions in the vacuole and synthesis of compatible solutes in the cytosol (Li et al 2010).…”
Section: Discussionmentioning
confidence: 79%